Food products based on Cannabis extract: from “Brisadeiro” to searching for a therapeutic effect (Research, Society and Development, 2022)
Introduction. Cannabis-based edibles have become a lucrative and in-demand market. Despite not being legalized in Brazil, marijuana is found in oral preparations illegally marketed in the country and the search for these products has grown in recent years. The present study aims to gather data from the scientific literature on the physiology of the endocannabinoid system, effects of oral cannabis consumption, pharmacokinetics, possible toxic and therapeutic effects and ways of detection, seeking to contribute to filling the gap that still exists on the theme. Methodology. An integrative review was carried out in the PubMed database for publications of the last 5 years in Portuguese, English and Spanish. Results. The search resulted in 128 articles from which the works that did not meet the inclusion criteria were removed, leaving 28 articles used. Conclusions. It is necessary to carry out a greater number of clinical trials with oral cannabis, in the various existing formulations, to better understand its pharmacokinetics, pharmacodynamics, therapeutic potential and its adverse effects.